Enantioseparation with cationic β-cyclodextrin chiral stationary phases in supercritical fluid chromatography and high-performance liquid chromatography - Wang, Renqi (2011)
Drug chirality has attracted attention as it will influence the pharmacological activities of racemic drugs. In order to get optically pure drugs, both analytical and preparative grade chiral separation technology has been developed. Since the first introduction of anionic moiety into β-cyclodextrin by Stalcup et al, the highly enantioseparation abilities of anionic β-cyclodextrin towards basic racemates have attracted chromatographers attention. Endeavors were then made on the synthesis and application of anionic beta-cyclodextrin for enantioseparation. However, positive charged β-cyclodextrin derivatives were rarely investigated. Lesser work was reported on enantioseparations with cationic β-cyclodextrin derivatives as chiral additives in reversed phase liquid chromatography or capillary electrophoresis whereas no work reported about the usage of cationic β-cyclodextrin derivatives as chiral stationary phases. In our work, cationic β-cyclodextrin derivatives are either physically coated or chemically bonded onto the surface of 5 pm spherical silica and applied as chiral stationary phases in HPLC and SFC. The cationic β-cyclodextrin derivatives have shown strong chiral separation abilities towards high medical value racemates and some propriety racemates.